2021
DOI: 10.1038/s41401-021-00721-5
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin protects glomerular podocytes by targeting Bcl-2-mediated autophagy and apoptosis in diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is one of the microvascular complications of diabetes mellitus and a major cause of end-stage renal disease with limited treatment options. Wogonin is a flavonoid derived from the root of Scutellaria baicalensis Georgi, which has shown a potent renoprotective effect. But the mechanisms of action in DKD are not fully elucidated. In this study, we investigated the effects of wogonin on glomerular podocytes in DKD using mouse podocyte clone 5 (MPC5) cells and diabetic mice model. MPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…The hyperglycemic state of diabetic rats increases the accumulation and expression of Beclin-1 simultaneously promoting retinal Müller cell death in rats ( Lopes de Faria et al, 2016 ). Beclin-1 and Bcl-2 are interrelated and their binding downregulates Beclin-1-mediated autophagy in diabetic nephropathy ( Xu and Qin, 2019 ; Liu et al, 2022 ). TFEB, a regulatory factor, is associated with lysosomal biosynthesis.…”
Section: Regulatory Factors Of Autophagy and Diabetesmentioning
confidence: 99%
“…The hyperglycemic state of diabetic rats increases the accumulation and expression of Beclin-1 simultaneously promoting retinal Müller cell death in rats ( Lopes de Faria et al, 2016 ). Beclin-1 and Bcl-2 are interrelated and their binding downregulates Beclin-1-mediated autophagy in diabetic nephropathy ( Xu and Qin, 2019 ; Liu et al, 2022 ). TFEB, a regulatory factor, is associated with lysosomal biosynthesis.…”
Section: Regulatory Factors Of Autophagy and Diabetesmentioning
confidence: 99%
“…The STZ-induced DN model was established using C57/J male mice aged 6-8 weeks, which were divided into two groups: The DN group (n = 6) and NC group (n = 6). The modeling method was processed as previously described (Liu et al, 2021). Mice in the two groups were kept in standard environment for 12 weeks after the success of the diabetes model.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Paraffin sections of the kidney tissue were dewaxed, repaired as previous (Liu et al, 2021), and then incubated with the primary antibody overnight at 4 °C after antigen blocking with hydrogen peroxide and 10% BSA, followed by application of the secondary antibody at 37 °C for 1 h. ImageJ software was used for IHC analysis.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products or traditional Chinese medicines have been long used in patients and considered an alternative therapeutic strategy for prevention and treatment of glomerular-associated diseases including MN ( Feng et al, 2020 ), glomerulonephritis ( Gianassi et al, 2019 ; Wang et al, 2021 ), diabetes ( Chen et al, 2020b ; Wang et al, 2020b ; Fang et al, 2021 ; Su et al, 2021 ; He et al, 2022 ), and diabetic nephropathy ( Li et al, 2020a ; Yang et al, 2020 ; Wang, 2021 ; Xuan et al, 2021 ; Yang and Wu, 2021 ; Zhou et al, 2021 ; Liu et al, 2022 ). Earlier finding have demonstrated that a 77-year-old woman with IMN was treated by Astragalus membranaceus and achieved clinical remission without using immunosuppressive therapy ( Ahmed et al, 2007 ).…”
Section: Treatment Of Membranous Nephropathymentioning
confidence: 99%